2020
DOI: 10.1055/a-1132-5371
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and barriers for implementation of the resect and discard strategy: an international survey

Abstract: Background and study aims Optical real-time diagnosis (= resect-and-discard strategy) is an alternative to histopathology for diminutive colorectal polyps. However, clinical adoption of this approach seems sparse. We were interested in evaluating potential clinical uptake and barriers for implementation of this approach. Methods We conducted an international survey using the “Google forms” platform. Nine endoscopy societies distributed the survey. Survey questions measured current clinical uptake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Attitudes of endoscopists and patients with regards to a leave-in-situ strategy Willems et al performed an international survey among 808 endoscopists from nine endoscopy societies to evaluate their attitudes and practices with regards to a leave-in-situ strategy [34] In total, 63 % of the participants partly or completely agreed that diminutive polyps could be left unresected until the next screening colonoscopy because of the low associated cancer risk. Endoscopists were evenly split on the effects of leaving such polyps unresected, with about 50 % thinking that leaving diminutive polyps in place would increase the cancer risk of patients.…”
Section: Pathological Accuracy and Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes of endoscopists and patients with regards to a leave-in-situ strategy Willems et al performed an international survey among 808 endoscopists from nine endoscopy societies to evaluate their attitudes and practices with regards to a leave-in-situ strategy [34] In total, 63 % of the participants partly or completely agreed that diminutive polyps could be left unresected until the next screening colonoscopy because of the low associated cancer risk. Endoscopists were evenly split on the effects of leaving such polyps unresected, with about 50 % thinking that leaving diminutive polyps in place would increase the cancer risk of patients.…”
Section: Pathological Accuracy and Reproducibilitymentioning
confidence: 99%
“…Attitudes of endoscopists and patients with regards to a resect-and-discard strategy When Willems et al asked endoscopists in their worldwide survey about barriers to implementation of a resect-and-discard strategy, it appears the clinical uptake of resect-and-discard is low [34]. They found that only 15.8 % of the endoscopists used the resect-and-discard strategy in their current practice and 59.9 % thought that implementation of the resect-and-discard strategy was not feasible in its current form.…”
Section: Risk Of Metastatic Disease After Resecting and Discarding A Diminutive Lesion With Cancermentioning
confidence: 99%
“…Although the concept of resect-and-discard presents a great potential to improve colonoscopy practice, its widespread clinical implementation has not been achieved. A recent survey revealed that endoscopists have failed to adopt the use of the resect-and-discard strategy in clinical practice because of concerns about making the wrong diagnosis and subsequently an erroneous surveillance interval assignment, with its potential medicolegal repercussions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Optical diagnosis can distinguish between neoplastic and non-neoplastic polyps and therefore deliver clinical and cost benefits by reducing the number of unnecessary histopathology examinations and providing immediate surveillance interval recommendations to patients. However, despite the demonstrated high accuracy of optical diagnosis for diminutive polyps, endoscopists have been reluctant to support its broad implementation because of concerns about incorrect diagnoses, assignment of inappropriate surveillance intervals, and related medicolegal issues[ 16 ].…”
Section: Introductionmentioning
confidence: 99%